Azobenzene-based ruthenium(ii) catalysts for light-controlled hydrogen generation. Issue 11 (27th February 2017) - Telleria, A.; van Leeuwen, P. W. N. M.; Freixa, Z.
Abstract : Photo-controlled hydrogen generation catalysts were developed based on ruthenium(ii ) azobenzene-containing half-sandwich complexes. Abstract : Eight new ruthenium(ii ) half-sandwich complexes containing azobenzene-appended pyridine (1 ), bipyridine (2–5 ) and phosphine (6 and7 ) ligands have been synthesized and fully characterized. UV-vis spectroscopic studies showed that the trans -to- cis photoisomerization was strongly inhibited upon coordination to the metal centre in azopyridine-derived ligands1 and2, but it remained efficient in azobenzene-appended bipyridine (3–5 ) and phosphine (6 and7 ) ligands. The complexes were tested as precatalysts for photo-controlled hydrogen generation by hydrolytic decomposition of ammonia-borane (AB). In situ irradiation of the reaction mixtures of compounds [Ru( p -Cym)(6 )Cl]Cl and [Ru( p -Cym)(7 )Cl]Cl induced a clear change in the catalytic reaction rate, serving as a proof of concept for light-controlled hydrogen generation.